TECHNOLOGY ACCEPTANCE MODEL: ACCEPTANCE OF DIGITAL NOVELS AMONG NOVEL READERS - Regozamil Reo; Achmad Algadri R; Yeremia S Ginting (Jurnal TAM (Technology Acceptance Model), 2019)
The readers' acceptance of novels in digital format is an important thing that must be understood, given the huge market potential of the novel. Although digital novels offer many conveniences, not necessarily readers who have enjoyed digital novels will continue to use. So, this study aims to find out whether other factors such as perceived convenience and perceived price as an external factor in the Technology Acceptance Model (TAM) also influence the readiness of individuals to continue using digital novels. This study uses a quantitative descriptive approach. The sampling technique uses judgmental sampling, with a sample of 200 digital novel readers. Data analysis used in the statistical analysis of this study is SEM-LISREL. The results of this study indicate that perceived convenience and perceived price together with the variables perceived ease of use and perceived usefulness have a positive effect on attitude toward using. The attitude toward using has a positive effect on the behavioral intention to use, and the intention to use also has a positive effect on actual system use, where actual system use also has a positive effect on satisfaction when using a digital novel and has implications for the intention to continue using the digital novel.The readers' acceptance of novels in digital format is an important thing that must be understood, given the huge market potential of the novel. Although digital novels offer many conveniences, not necessarily readers who have enjoyed digital novels will continue to use. So, this study aims to find out whether other factors such as perceived convenience and perceived price as an external factor in the Technology Acceptance Model (TAM) also influence the readiness of individuals to continue using digital novels. This study uses a quantitative descriptive approach. The sampling technique uses judgmental sampling, with a sample of 200 digital novel readers. Data analysis used in the statistical analysis of this study is SEM-LISREL. The results of this study indicate that perceived convenience and perceived price together with the variables perceived ease of use and perceived usefulness have a positive effect on attitude toward using. The attitude toward using has a positive effect on the behavioral intention to use, and the intention to use also has a positive effect on actual system use, where actual system use also has a positive effect on satisfaction when using a digital novel and has implications for the intention to continue using the digital novel.